Vanilla authenticity control by DNA barcoding and isotope data aggregation - Geißler, Katrin; Greule, Markus; Keppler, Frank (Flavour and fragrance journal, 2017)
Originating from the seedpods of orchids, Vanilla belongs to the most widely appreciated flavours worldwide. Besides the seedpods (beans) also Vanilla extracts and isolated vanillin as the major characteristic aroma compound are commercially used. Different consumer demands and national regulations require appropriate quality control of products arising from the Vanilla plants. Depending on the kind of product and its position in the supply or value chain, different methods for quality control and authentication have to be applied. When examining plant material for instance DNA barcoding can be used, whereas for Vanilla extracts and vanillin analytical quality control is frequently employed. As one of the first chemically synthesized flavouring substances with its first production in the late 19th century vanillin is nowadays manufactured via multiple different chemical and natural routes. To discriminate commercial vanillin qualities by their precursors with respect to the chemical and natural origin stable isotope ratio mass spectrometry (sIRMS) and 1H nuclear resonance spectroscopy (NMR) are the most recognized techniques. This article describes new features to discriminate vanillin from different origins using the δ13C and δ2H ratios of the methoxy group after derivatization with hydriodic acid and subsequent measurement of the released gaseous methyl iodide (CH3I) with sIRMS. The combination of available analytical data by means of multiparametric statistical tools allows for the clear segregation of critical provenience clusters for vanillin, such as (natural) eugenol-derived qualities from (synthetic) lignin- or curcumin-based products. The approach supports quality and authenticity control for Vanilla-based products, aiding in meeting customer expectations in this demanding market segment.